2005
DOI: 10.1007/s10800-005-9012-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cathode material LiNi1-y Co y O2 by a simplified combustion method

Abstract: The optimum conditions for synthesizing LiNi 1-y Co y O 2 (y=0.1, 0.3 and 0.5) by a simplified combustion method, in which the preheating step is omitted, and the electrochemical properties of these materials were investigated. The optimum condition for synthesizing LiNi 0.9 Co 0.1 O 2 by the simplified combustion method is calcination at 800°C for 12 h in air in 3.6 mole ratio of urea to nitrate. The LiNi 0.9 Co 0.1 O 2 synthesized under these conditions shows the smallest R-factor{(I 006 +I 102 )/I 101 } and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This indicates that, this is the best annealing condition to synthesize 333Fe using this method which is in agreement with the values of I(003)/I(104) and R-factor shown in Table 1. This sample possesses the highest hexagonal order among those annealed at 800 ˚C as well as the one with the least cation mixing [10]. It also can be observed that the sample annealed at 800 ˚C for 24 h exhibits the worst performance with not only the lowest discharge capacity, but it also suffers the largest capacity loss after ten cycles.…”
Section: Phase Analysismentioning
confidence: 82%
See 1 more Smart Citation
“…This indicates that, this is the best annealing condition to synthesize 333Fe using this method which is in agreement with the values of I(003)/I(104) and R-factor shown in Table 1. This sample possesses the highest hexagonal order among those annealed at 800 ˚C as well as the one with the least cation mixing [10]. It also can be observed that the sample annealed at 800 ˚C for 24 h exhibits the worst performance with not only the lowest discharge capacity, but it also suffers the largest capacity loss after ten cycles.…”
Section: Phase Analysismentioning
confidence: 82%
“…In general, the cyclability of the 333Fe compounds are good with all the materials exhibit small capacity loss, except the one annealed at 800˚ C for 24 h which suffers more than 10 % capacity loss after ten cycles. The cyclability is improved as the annealing temperature increased due to the improved crystallinity from multi-phase transition to single phase transition [10].…”
Section: Phase Analysismentioning
confidence: 99%
“…LiCoO 2 cathode has a well-ordered layered crystal structure and fast lithium extraction/insertion but it suffers from three major restrictions which is toxicity, scarcity and cost [1]. Lithium manganese oxides LiMn 2 O 4 was introduced as a safer and cheaper material [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the electrochemical properties of LiNiO 2 , Co [17][18][19][20][21], Al [22][23][24][25], Ti [26][27][28][29][30], Ga [31], Mn [32] and Fe [33][34][35][36] ions were substituted for lithium ion. Rougier et al [18] reported that the stabilization of the two-dimensional character of the structure by cobalt substitution in LiNiO 2 is correlated with an increase in the cell performance due to the decrease in the amount of extra-nickel ions in the inter-slab space which impede the lithium diffusion.…”
Section: Introductionmentioning
confidence: 99%